2014
DOI: 10.1007/s10803-014-2226-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in Adolescent Boys with Autism Spectrum Disorder: Self-reported Behaviours and Attitudes

Abstract: Differences in sexual functioning of adolescents with and without autism spectrum disorder (ASD) are understudied. In the current study, self-reported sexual behaviours, interests and attitudes of 50 adolescent boys, aged 15-18, with at least average intelligence and diagnosed with ASD, were compared with a matched general population control group of 90 boys. Results demonstrated substantial similarity between the groups in terms of sexual behaviours. The only significant difference was that boys with ASD reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 45 publications
3
81
1
6
Order By: Relevance
“…Researchers in the field of sexual development and functioning in adolescents and adults with ASD have already stressed the need for early and comprehensive sex education (CSE) including attention to relational and social skills (e.g. Attwood et al, 2014;Byers and Nichols, 2014;Dewinter et al, 2015;Stokes, 2007;Stokes and Kaur, 2005).…”
Section: Clinical Implications: Discussing Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Researchers in the field of sexual development and functioning in adolescents and adults with ASD have already stressed the need for early and comprehensive sex education (CSE) including attention to relational and social skills (e.g. Attwood et al, 2014;Byers and Nichols, 2014;Dewinter et al, 2015;Stokes, 2007;Stokes and Kaur, 2005).…”
Section: Clinical Implications: Discussing Experiencementioning
confidence: 99%
“…Most studies on sexuality in individuals with ASD, as in the case of the general population, focus on the prevalence of sexual behaviours and on sexual knowledge (Dewinter et al, 2013;Kellaher, 2015). Studies based on self-report (Byers et al, 2012(Byers et al, , 2013Dewinter et al, 2015;Mehzabin and Stokes, 2011;Ousley and Mesibov, 1991) and parental or caregiver reports (Haracopos and Pedersen, n.d.;Hellemans et al, 2007Hellemans et al, , 2010Holmes and Himle, 2014;Stokes and Kaur, 2005) have shown that sexuality is a part of life for individuals with ASD. Especially highfunctioning adolescents and adults with ASD reported or demonstrated interest in relationships and partnered sexuality (Haracopos and Pedersen, n.d.).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been previously proposed that children with ASD are sexually immature, unaware of sexuality, and not interested in sexuality [3,4], findings from recent studies show that the sexuality of these children is clinically similar to that of their peers who are not affected by ASD [5,6]. Seventy-five percent of children with ASD exhibit various sexual behaviours [4].…”
Section: Introductionmentioning
confidence: 99%
“…Further, social engagement has been found to mediate the association between ASD and sex‐related education, and that when sex‐related education is held stable, the association between ASD and social engagement is no longer statistically significant [Stokes & Kaur, ]. Previous studies have found less experience in romantic relationships reported by those with ASD [Holmes & Himle, ], while others have found similar rates across groups [Dewinter, Vermeiren, Vanwesenbeeck, Lobbestael, & Van Nieuwenhuizen, ].…”
Section: Introductionmentioning
confidence: 99%